Meningkatkan Daya Saing Perusahaan Elektrikal Mekanikal PT Cipta Lestari Teknik Melalui Analisis Matriks SWOT dan Penetapan Strategi yang Efektif - Febiati, Fika; Maya Kristanti; Natanael Murjono; Retno Wulandari Putri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In an era of increasingly competitive business competition, companies are required to have the right strategy to maintain and improve their competitiveness. This study aims to analyze the internal and external factors that affect the competitiveness of PT Cipta Lestari Teknik, a company engaged in research materials, through a SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats). This method is used to identify the strengths, weaknesses, opportunities, and threats faced by the company, and determine the company's position in the SWOT matrix. Furthermore, the results of the analysis are used as the basis for formulating the most effective strategy to improve the company's competitiveness. The results showed that the company has significant strengths such as a competent research team, modern equipment, and an extensive network of relationships, with an IFAS value of 0.85. On the other hand, external opportunities such as increasing research demand and government support resulted in an EFAS value of 1.00. Based on the SWOT matrix, PT Cipta Lestari Teknik's strategic position is in the growth quadrant, which shows high growth potential. Recommended strategies include intensive strategies such as market penetration and product development. The study also assessed the ability of discussion participants to understand and implement SWOT analysis concretely and evaluate the effectiveness of the proposed strategy, including consideration of potential risks and opportunities. The establishment of a directed strategy based on SWOT analysis is expected to increase the company's competitiveness in a sustainable manner.